Review of Trousseau phenomenon - pathomechanism, diagnosis, treatment and risk of cancer - Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria; Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Broda, Aleksandra; Hoksa, Kacper; Jodłowski, Krzysztof; Dubniewicz, Ewa (Journal of Education, Health and Sport, 2025)
Introduction: Trousseau's phenomenon, also referred to as malignancy-associated thrombosis, represents a hypercoagulable state commonly encountered in oncology patients, contributing substantially to morbidity and mortality. This review examines the underlying mechanisms of Trousseau’s phenomenon, including the release of tumor-derived procoagulants and immune-inflammatory interactions, alongside contemporary diagnostic methodologies and emerging biomarker candidates. Additionally, therapeutic strategies, with a focus on anticoagulation management, are discussed, highlighting the clinical and prognostic significance of Trousseau’s phenomenon in evaluating cancer progression and risk stratification. The evolving understanding of this condition underscores the necessity of interdisciplinary collaboration in its clinical management and ongoing research efforts. Aim of these study: The aim of this study was to explore the issue of hypercoagulability in the cancer patient population and to investigate the underlying mechanisms contributing to its development. State of knowledge: It is well-established in scientific literature that oncology patients are at a significantly increased risk for thromboembolic events. Neoplasms promote a hypercoagulable state and its associated complications through diverse and complex pathophysiological mechanisms. Conclusions: Cancer-associated thrombosis is a significant clinical challenge in oncology patients. Understanding the underlying mechanisms, identifying specific risk factors, and ensuring early diagnosis are essential for improving prognosis and optimizing therapeutic outcomes.